109: RISK MANAGEMENT AND PATIENT SAFETY IN OPERATING ROOM: A SYSTEMATIC REVIEW. (8th February 2017) - Kabiri, Neda; Jannati, Ali; Vahed, Nafiseh; Oskouei, Mina Mahami
Abstract : Background and aims: The concept of risk management is a new issue which pointed out the dangers of the health system on patients. Statistics indicate that a non-negligible percentage of patients, faced with health system, especially hospitals, and injuries are complications arising from the provision of services. Since the entire process of provision of health services is combined with a degree of safety and risk, therefore, safety is one of the most fundamental principles of service delivery in health centers. This study was a systematic review of risk management and patient safety in operating room. Methods: We systematically reviewed the literature from PubMed (Medline), The Cochrane Library, Ovid, Scopus, Embase, Proquest and Google Scholar published between 2000 and 2016. The search strategy Included a combination of key words "Risk Management", "Patient Safety", "Operating Rooms" in all fields. Also the publication types of review and articles were included and meetings abstracts, editorials, brief commentaries, letters, errata and papers that Subtopics were also excluded. Results: The initial search identified 340 abstracts. Application of the inclusion/exclusion criteria resulted in 24 articles for review. The majority of studies mentioned well communication between patient and operating team, Steps to prevent wrong-site, wrong-person and wrong-procedure errors, checklist using and Teamwork as effective interventions. Conclusion: Results from this project gives healthcare managers, policy makers, and operating room staff useful information to increase surgical rooms efficiency and patient safety.